Pendidikan (Peningkatan Kompetensi) Guru - Eka Mayasari; Syarif , Muhammad (JURNAL ILMU PENDIDIKAN, 2024)
The teacher's competencies are as follows: 1) Paedagogic Competence, is the teacher's understanding of students, designing and implementing learning, evaluating learning outcomes and developing students to actualize their various potentials. 2) Personal competence, is a personal ability that reflects a solid, stable, mature, wise and authoritative personality and becomes a role model for students and has noble character. 3) Social Competence, is the teacher's ability to communicate and interact effectively with students, fellow educators, educational staff, parents/guardians of students and the surrounding community. 4) Professional Competence, competency in mastering learning material broadly and in depth which includes mastery of curriculum subject matter in schools and the scientific substance that overshadows the material. Competency development efforts are the ability of a teacher to carry out obligations in a responsible and appropriate manner to achieve effective and efficient learning outcomes. Efforts to develop teacher competence are as follows: 1) certification program, 2) increasing teacher competency and professionalism, 3) participating in teacher upgrading, 4) attending teacher deliberations in subject areas, 5) attending courses, and 6) increasing knowledge through mass media or the media electronic.